If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + w = 8w Solving 42 + w = 8w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-8w' to each side of the equation. 42 + w + -8w = 8w + -8w Combine like terms: w + -8w = -7w 42 + -7w = 8w + -8w Combine like terms: 8w + -8w = 0 42 + -7w = 0 Add '-42' to each side of the equation. 42 + -42 + -7w = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -7w = 0 + -42 -7w = 0 + -42 Combine like terms: 0 + -42 = -42 -7w = -42 Divide each side by '-7'. w = 6 Simplifying w = 6
| -10y-19=19-8y | | P=M(1+dn) | | x^2-5x+7x-2=0 | | 2ln*2x^2/2 | | y-1=3/7x | | (x-2)=180 | | X=26+16 | | 4.2g=63 | | X=29+8 | | 3x/6=12/4 | | 2*ln*2x^2=1 | | 1/5(5)^2 | | X=29+19 | | 2x^2-3x-9=-4 | | (x-2)=(x-3) | | 4q-15=13 | | 7/4=21/x | | 2/5-2×10 | | 15x+12y=112 | | 6x+15=9x-15 | | 5x+3x=1 | | 17-2x+17=7+17 | | (v+2)(v-8)=0 | | 2x+5x=11+3 | | M=C(1+dN) | | 10=p-22 | | 0.2+x=30 | | 5x-14+2x=100+3x-34 | | 32(6x+2)= | | 7p-8=6p+34 | | 5(3+m)=35 | | 44+s=41 |